Acquired subepidermal bullous diseases associated with psoriasis: a clinical, immunopathological and immunogenetic study. - Kirtschig, G; Chow, E; Venning, V; Wojnarowska, F (1996)
Clinical, immunopathological and immunogenetic studies of four patients with a subepidermal bullous disease associated with psoriasis were carried out to determine the true nature of the blistering disease and to investigate further the relationship between psoriasis and acquired subepidermal bullous diseases. Autoantibodies in all four patients bound to the epidermal side of salt-split skin by indirect immunofluorescence and detected the major bullous pemphigoid (BP) antigens by immunoblotting. One had additional IgA autoantibodies binding an epidermal polypeptide of 270/280 kDa and another had circulating IgG autoantibodies which detected both BP and epidermolysis bullosa acquisita (EBA) antigens. All patients had active psoriasis at the onset of the bullous disease. Three patients were being treated with tar when blisters developed; one patient also received UVB radiation and experienced a relapse after exposure to sunlight. HLA phenotypes in three patients were determined. All the patients responded well to methotrexate. These findings demonstrate that BP is the subepidermal bullous disease most associated with psoriasis. Changes at the basement membrane zone in psoriasis may be responsible for the heterogeneous antibody response and may trigger the bullous disease, as may antipsoriatic treatment including tar and UV radiation. However, common immunogenetic mechanisms may play a crucial part in this disease association.